Prevalence and Patterns of Oral Mucosal Lesions Among Geriatric Patients in India: A Retrospective Study - Kumar Ankit; Yusra Khan; Avinash Jaiswal; Deepmala Rana; Ahtesham Ahmad Qurishi; Shreya Pandey; Pranav V. Manek (Wolters Kluwer Medknow Publications, 2024)
Introduction: Geriatric dentistry plays a pivotal role in addressing the oral health needs of the elderly population, who are prone to various age-related disorders affecting the oral mucosa. This study aims to investigate the prevalence of oral mucosal lesions among geriatric patients in India, considering factors, such as age, gender, and systemic diseases. Methodology: A hospital-based retrospective study was conducted, analyzing medical and clinical examination records of 354 geriatric patients attending a dental college/hospital between 2022 and 2023. Data on demographics, systemic diseases, oral habits, and denture usage were collected, and oral mucosal lesions were classified according to the World Health Organization (WHO) criteria. Results: Among the 354 subjects examined, oral mucosal lesions were observed in 54.66% of cases. Leukoplakia (19.49%) and lichen planus (17.80%) were the most prevalent lesions, followed by malignancy (12.99%) and denture stomatitis (9.04%). The prevalence varied across age-groups, with higher rates observed in individuals aged 60-70 years. Conclusion: The study highlights the significant burden of oral mucosal lesions among geriatric patients in India, underscoring the need for targeted preventive strategies and comprehensive oral healthcare interventions tailored to the specific needs of elderly individuals.